Florida, Richard (2017). The New Urban Crisis: How Our Cities Are Increasing Inequality, Deepening Segregation, and Failing the Middle Class—and What We Can Do About It - Vergara Perucich, Jose Francisco (Documents d'Anàlisi Geogràfica, 2019)
Florida, Richard (2017) The New Urban Crisis: How Our Cities Are Increasing Inequality, Deepening Segregation, and Failing the Middle Class—and What We Can Do About It Nova York: Basic Books, 336 p. ISBN 9780465079742